2005
DOI: 10.1038/sj.onc.1208695
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pigment epithelium-derived factor as a direct target of the p53 family member genes

Abstract: p63 and p73 show a high degree of structural homology to p53 and are members of a family of transcriptional factors that can activate transcription of p53-responsive genes. p53 is mutated in more than 50% of human cancers, whereas p63 and p73 are rarely mutated. Studies of knockout mice also revealed an unexpected functional diversity among the p53 family. To determine how p63 and p73 are involved in tumorigenesis and normal development, we used cDNA microarray to examine 9216 genes in human colorectal cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Recent studies indicate that p63 proteins can bind DNA through response element (p63RE) slightly different to p53RE conferring responsiveness to p63 but not p53 proteins. 18,19 The DNp63 isoforms can bind DNA through p53RE and can exert dominant-negative effects over p53, p73 and p63 activities by either competing for DNA binding sites or by direct protein interaction (for a review Benard et al 20 ). DNp63 isoforms were also shown to directly activate specific gene targets not induced by TA isoforms.…”
Section: P63mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that p63 proteins can bind DNA through response element (p63RE) slightly different to p53RE conferring responsiveness to p63 but not p53 proteins. 18,19 The DNp63 isoforms can bind DNA through p53RE and can exert dominant-negative effects over p53, p73 and p63 activities by either competing for DNA binding sites or by direct protein interaction (for a review Benard et al 20 ). DNp63 isoforms were also shown to directly activate specific gene targets not induced by TA isoforms.…”
Section: P63mentioning
confidence: 99%
“…Recent studies indicate that p73 proteins can bind DNA through response element slightly different to p53RE conferring responsiveness to p73 but not p53 proteins. 19 Biological activities of the p73 isoforms So far, there have been limited data concerning the expression patterns of individual p73 proteins, due to a lack of antibodies that distinguish between the different isoforms. The p73 gene is expressed in all normal tissues studied to date, although expression is at very low level.…”
Section: P63 and Cancermentioning
confidence: 99%
“…These results demonstrate that p63 binds to the VDR promoter in vivo. Detailed analysis of the promoter region of p63 responsive genes has resulted in the identification of responsive elements that are specifically activated by p63 (Osada et al, 2005;Sasaki et al, 2005). The p63 responsive element appears to differ from the canonical (RRRCWWGYYY) responsive element of p53 in the CWWG core binding element as well as in the flanking RRR and YYY stretches (Osada et al, 2005).…”
Section: Identification Of Vitamin D Receptor As a Target Of P63mentioning
confidence: 99%
“…Next, we wanted to investigate whether upregulation of VDR by p63 results in differentiation in SaoS2 (osteosarcoma) cells (Sasaki et al, 2005). SaoS2 cells transiently transfected with p63g showed a significant increase in number of cells with elongated cytoplasmic processes and flattened fibroblastic appearance.…”
Section: Identification Of Vitamin D Receptor As a Target Of P63mentioning
confidence: 99%
“…TAp63g has also been shown to activate the expression of Jagged 1 and Jagged 2, which are involved in Notch signaling, whereas Notch 1 activation has also been shown to suppress DNp63a expression, demonstrating a cross-talk between these pathways (7,8). Additional studies have shown that the biological effects of p63 in development and tumor suppression is exerted through the regulation of multiple signaling pathways (9)(10)(11)(12)(13)(14)(15)(16)(17). p73, another member of the p53 family, was also discovered based on structural similarities to p53 (18).…”
Section: Introductionmentioning
confidence: 99%